Mood state of runners participating in an elite developmental training camp - Coyle, M. A.; Raglin, J. S.; Stager, J. M. (Medicine & Science in Sports & Exercise, 1998)
Elite US middle and long-distance runners (M = 14; F = 7) participated in a five-week training camp at altitude (1,828-3,048 m) and lived at 2,438 m. Mood state (POMS) was assessed at weekly intervals. Total mood disturbance was unchanged during training and all assessments were well below the published norm. However, tension and fatigue elements were elevated when assessed in concert with major time trials. Implication: Mood state changes reflect responses to competitive stresses but not to altitude variations.